Optimizing Students' Scientific Attitudes and Collaboration Skills Through Problem-Based Learning Based on Tri Hita Karana - Ni Wayan Rati; Ketut Herya Darma Utami; I Made Hendra Sukmayasa; I Nyoman Tri Esaputra; Jian-bang Deng (Yayasan Keluarga Guru Mandiri, 2024)
The major problem in this study is students' lack of scientific mentality and collaborative skills when learning Natural and Social Sciences (IPAS), which conventional techniques have dominated. Traditional methods involve students less actively in problem-solving and group work, which hinders the ideal development of their scientific attitudes and collaborative skills. This study examines how the Problem-Based Learning (PBL) learning paradigm based on Tri Hita Karana affects fourth-grade students' scientific attitudes and collaborative skills, both individually and concurrently. This study used a quasi-experimental approach with a posttest-only control group. The research population consisted of all fourth-grade pupils, 105 individuals, with a sample of 70 picked using basic random selection procedures. The PBL learning model based on Tri Hita Karana is the independent variable, whereas the dependent variables are students' scientific attitudes and collaboration skills. Data were acquired by observation and analyzed using Multivariate Analysis of Variance (MANOVA) statistics. The findings revealed that the Tri Hita Karana-based PBL learning paradigm substantially impacted students' scientific attitudes and collaboration skills when learning IPAS. These findings indicate that implementing Tri Hita Karana-based PBL can effectively improve learning quality and develop elementary school students' attitudes and collaboration skills.